2021
DOI: 10.3390/pharmaceutics13070958
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Pharmacokinetics and Anti-Pulmonary Fibrosis-Related Effects of Sulforaphane and Sulforaphane N-acetylcysteine

Abstract: Sulforaphane (SFN), belonging to the isothiocyanate family, has received attention owing to its beneficial activities, including chemopreventive and antifibrotic effects. As sulforaphane N-acetylcysteine (SFN-NAC), a major sulforaphane metabolite, has presented similar pharmacological activities to those of SFN, it is crucial to simultaneously analyze the pharmacokinetics and activities of SFN and SFN-NAC, to comprehensively elucidate the efficacy of SFN-containing products. Accordingly, the anti-pulmonary fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
(35 reference statements)
1
4
0
Order By: Relevance
“…16 With a terminal half-life ranging between 42 min and 65.6 h in rats, SFN is ultimately conjugated with glutathione and further metabolized through the mercapturic acid pathway and excreted through the renal route. 47,50 Our present in vivo study showed that the plasma concentration of SFN was 0.124 μM after 12 weeks of BSE supplementation at a dose of 600 mg kg −1 diet, which is consistent with another report. 51 Nevertheless, the concentrations of SFN used in our in vitro study ranged from 1 μM to 10 μM, and the significant inhibitory effects were mainly observed at 5 μM and 10 μM.…”
Section: Papersupporting
confidence: 92%
See 3 more Smart Citations
“…16 With a terminal half-life ranging between 42 min and 65.6 h in rats, SFN is ultimately conjugated with glutathione and further metabolized through the mercapturic acid pathway and excreted through the renal route. 47,50 Our present in vivo study showed that the plasma concentration of SFN was 0.124 μM after 12 weeks of BSE supplementation at a dose of 600 mg kg −1 diet, which is consistent with another report. 51 Nevertheless, the concentrations of SFN used in our in vitro study ranged from 1 μM to 10 μM, and the significant inhibitory effects were mainly observed at 5 μM and 10 μM.…”
Section: Papersupporting
confidence: 92%
“…Studies have suggested that SFN is well absorbed in the intestine with oral bioavailability over 70% in rats. 46,47 Serum/plasma concentrations of free SFN largely depend on many factors, e.g. , the amount of GSL, myrosinases, and SFN in cruciferous vegetables (that mainly depends on the maturity rate and processing technology), gut flora, as well as the time points of testing after administration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, SFN-NAC was shown to readily convert to SFN in rats when administered orally and in plasma, and both had similar antipulmonary fibrotic effects. 11 In summary, SFN metabolites are readily reversible and yield free, bioavailable SFN.…”
Section: ■ Introductionmentioning
confidence: 99%